Investigating teachers' expectations from a professional development program for integrated STEM education - Filiz Mumcu; Nilüfer Atman Uslu; Bahadır Yıldız (Journal of Pedagogical Research, 2022)
Teacher qualifications are a crucial element for successfully implementing integrated STEM education. Research suggests that a STEM education program should be compulsory for all STEM-related teachers. In this study, as STEM education researchers, we asked teachers from different disciplines about their expectations from a professional development (PD) program for integrated STEM education. Six hundred sixty-four teachers participated in the study. We examined the PD expectations of middle school science, mathematics, and computer science teachers regarding pedagogical knowledge, technological knowledge, benefits, and PD program design. In addition, we discussed how these expectations changed based on teachers' subjects. Qualitative data were analyzed through content analysis. In terms of pedagogical knowledge, teachers want to use innovative approaches while integrating ICT into the learning and teaching process. Teachers' expectations of developing ICT competencies in terms of technological knowledge are at the forefront. In the design of such programs, the most critical expectations of teachers are to provide collaborative working environments, thus increasing their opportunities to work with colleagues from different disciplines and their capacity to do interdisciplinary work. Teachers' willingness to participate in a PD program related to integrated STEM education has four underlying expectations: student benefit, professional benefit, personal benefit, and context benefit. Teachers' expectations vary according to the subject area.